Conference Review: Once upon a Time... in Kernave - Magdalena Zielińska (EXARC Journal)
And so EXARC met again, this time in Lithuania, in Kernavė – an early medieval capital of the Grand Duchy of Lithuania. This picturesque village was the location for the conference “Archaeology for the People” which EXARC co-organised with the State Cultural Reserve of Kernavė and with IMTAL-Europe. The Reserve of Kernavė is an old member of EXARC. IMTAL-Europe is a long-time cooperation partner of EXARC; they are, as is IMTAL-Europe with whom we previously organised a conference. a network for live historic costumed Interpretation.